2020
DOI: 10.1177/0020852320935982
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Asian cultural values upon leadership roles and styles

Abstract: In light of an increasingly integrated society, in-depth research is needed to explore how particular perceived values may guide leadership behaviour by measuring the everyday actions of employees. As Asian individual values become collective, there is an increased likelihood that they will be perceived as cultural values that translate into expectations of leadership roles. This article considers the impact of changes in leadership roles from a role theory perspective, based on Asian values leading to changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Similarly, several other studies have confirmed the impact of manager demographic factors, namely, age, education and experience on firm performance (Kagzi and Guha, 2018; Díaz-Fernández et al , 2014; Post and Byron, 2015). Consequently, Arun and Kahraman Gedik (2020) also described that leadership styles significantly influence the decision-making process, middle managers activities and operational performance of organizations. Hence, based on this evidence, we expect that project manager demographic factors affect project performance.…”
Section: Literature Review and Building Hypothesesmentioning
confidence: 99%
“…Similarly, several other studies have confirmed the impact of manager demographic factors, namely, age, education and experience on firm performance (Kagzi and Guha, 2018; Díaz-Fernández et al , 2014; Post and Byron, 2015). Consequently, Arun and Kahraman Gedik (2020) also described that leadership styles significantly influence the decision-making process, middle managers activities and operational performance of organizations. Hence, based on this evidence, we expect that project manager demographic factors affect project performance.…”
Section: Literature Review and Building Hypothesesmentioning
confidence: 99%
“…Culture differs from society to society. Asian culture is different from European and American culture (Arun & KahramanGedik, 2022). Similarly, Asian English is different from European and American Englishes; it is because of differences in culture and society.…”
Section: Change In the Perspective Of Society Towards English Languagementioning
confidence: 97%
“…Communication is important to see acting leadership and look at the managers' approach (Gibson & Cohen, 2003;O'Neill et al, 2009). Communication style can be influenced by the difference between cross-cultural managers and the cultural frame (Arun & Kahraman-Gedik, 2020;Shah et al, 2020). This is what allows us to understand the reason for laissez-faire in Afghanistan or authoritative methods in Turkey.…”
Section: Virtual Management and Leadershipmentioning
confidence: 99%